Acute Febrile Respiratory Illness in the ICU - Sandrock, Christian (Chest, 2008)
Acute febrile respiratory illness (FRI) leading to respiratory failure is a common reason for admission to the ICU. Viral pneumonia constitutes a portion of these cases, and often the viral etiology goes undiagnosed. Emerging viral infectious diseases such as severe acute respiratory syndrome and avian influenza present with acute FRIs progressing to respiratory failure and ARDS. Therefore, early recognition of a viral cause of acute FRI leading to ARDS becomes important for protection of health-care workers (HCWs), lessening spread to other patients, and notification of public health officials. These patients often have longer courses of viral shedding and undergo higher-risk procedures that may potentially generate aerosols, such as intubation, bronchoscopy, bag-valve mask ventilation, noninvasive positive pressure ventilation, and medication nebulization, further illustrating the importance of early detection and isolation. A small number of viral agents lead to acute FRI, respiratory failure, and ARDS: seasonal influenza, avian influenza, coronavirus associated with severe ARDS, respiratory syncytial virus, adenovirus, varicella, human metapneumovirus, and hantavirus. A systematic approach to early isolation, testing for these agents, and public health involvement becomes important in dealing with acute FRI. Ultimately, this approach will lead to improved HCW protection, reduction of transmission to other patients, and prevention of transmission in the community.